Modulating electronic structure of metal-organic frameworks by introducing atomically dispersed Ru for efficient hydrogen evolution - Yamei Sun (Nature Portfolio, 2021)
Developing high-performance, neutral-media H2-evolution electrocatalysts is important for clean and sustainable hydrogen energy, yet rare, expensive elements are most active. Here, authors show that metal-organic frameworks modified with single ruthenium atoms as high-performances catalysts.